Slovenska podjetniška demografija in prenos podjetij: Slovenski podjetniški observatorij 2018 - Močnik, Dijana; Duh, Mojca; Crnogaj, Katja (University of Maribor Press, 2019)
Slovenian Enterprise Demography and Business Transfer: Slovenian Entrepreneurship Observatory 2018. In this monograph, we analysed all companies and entrepreneurs in Slovenia for the year 2017, then we compared for the year 2016 or 2015 key data of Slovenia and EU-28 or individual member states in the non-financial business economy. In Slovenia, in 2017 122,618 businesses employed 563,356 people. The majority of businesses (nearly one fifth) operated in the wholesale and retail trade; maintenance and repair of motor vehicles. Likewise, in the EU-28 in 2016 more than a quarter of businesses (25.9% or 6.3 million) was active in the wholesale and retail trade; maintenance and repair of motor vehicles. The average value added per person employed for the aggregated activities of the EU-28 in the year 2016 amounted to 50,900 euros, while in Slovenia 32,700 euros (36% less). In the second part, we studied the transfer of companies. We surveyed a selected sample of experts who represent important actors in a supportive environment for SME transfers. We also carried out a survey on the transfer of companies among the founders/owners of SMEs in Slovenia. We were interested in what type of support they need in this process. In this, we limited ourselves to the age group of entrepreneurs 55+.